Comprehensive Guidance: A Model For Guidance and Counseling At Senior High Schools - Nurihsan, Juntika (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2009)
This work is a summary of a study conducted to propose a model to enhance quality and management system for guidance and counseling services at public Senior High Schools (hereafter Indonesian SMANs). The model resulted is called A Model for Comprehensive Guidance developed conceptually and empirically based on field study at SMAN 1 Padang, SMAN 1 Tangerang, SMAN 1 Manado, SMAN 1 Bali, and SMAN 1 Kupang. The finding upon completion of the study is in the form of a comprehensive model for guidance comprising components of comprehension and philosophical grounds, the vision and mission of the guidance, students’ needs, content of the guidance and, the supporting system.